Coopetition research - A systematic literature review on recent accomplishments and trajectories - Gernsheimer, Oliver; Kanbach, Dominik K.; Gast, Johanna (Industrial marketing management, 2021)
Research in the field of coopetition, which describes firms simultaneously competing and collaborating to create value, has recently gained enormous momentum. Over the period of 2015 to 2020, scholars published more high-quality studies on this subject than in the entire 25-year history of coopetition research. Despite the relevance of these contributions, their fragmented nature and disjuncture from prior studies limit a connected understanding of the current standing of the field. Our analysis addresses this gap by systematically reviewing, comparing, and connecting a selected sample of 161 recent articles with the body of research established prior to 2015. Our study makes three main contributions. We (1) structure and connect past and present coopetition research across five identified research dimensions: Antecedents, execution, interaction, outcomes, and levels of coopetition. We (2) supplement this review with a qualitative trend analysis, identifying emerging themes for the future of the field. By combining past and present perspectives with the future outlook, we (3) provide a comprehensive, unique, and updated perspective on coopetition research, unifying it into a cohesive, overarching framework. Lastly, we explain crucial interdependencies and suggest areas for future research before we conclude the study. •Research on coopetition has significantly surged in recent years.•Our systematic literature review structures and connects past and present accomplishments in coopetition research. .•Supplemented by a qualitative trend analysis, we identify emerging trends for the future development of the field.•Our coopetition framework guides new research projects and the practical implementation of coopetition strategies.